Estimation of age from pulp chamber volume of first molars and second premolars using CBCT in central Indian population: An analytical study - Vidyarjan Sukhadeve; Ramhari Sathawane; Ashish Lanjekar; Romita Gaikwad; Dhiran Talatule; Charwak Tayade (Journal of Indian Academy of Oral Medicine and Radiology, 2023)
Introduction: Teeth form a suitable parameter for age estimation as they disintegrate very slowly and are impervious to injuries. CBCT imaging not only allows observation of changes within teeth but permits observations of living specimens. Pulp chamber size may show a significant relationship with chronological age. Aim: To estimate the age from pulp chamber volume of first molars and second premolars using CBCT and compare it to the actual age. Materials and Methods: The current study comprised 115 subjects which were divided into four age groups. DICOM CBCT images were exported to ITK SNAP 3.8 software. Pulp chamber volumes were measured using voxel counting and image segmentation tools. Results: Molars predict the age with an accuracy of 55% and 52.1%, whereas premolars predict the age with an accuracy of 35% and 33.4% in males and females, respectively. Discriminant equations are derived for maxillary and mandibular molars and premolars irrespective of age groups, age-wise, and gender-wise groups for age estimation. Conclusion: Maxillary molars and mandibular premolars are found as strong predictors of age. CBCT imaging has proved as an excellent tool with precision and accuracy and is recommended for use in age estimation.